2009
DOI: 10.1136/ard.2009.117572
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-gamma gene polymorphisms associated with susceptibility to systemic lupus erythematosus

Abstract: Several SNP in IFNG are associated with SLE susceptibility, and the risk allele of an associated SNP (rs2430561) located in an NF-kappaB binding site has elevated IFNG expression versus the non-risk allele, supporting that elevated IFNG expression is associated with increased SLE susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 17 publications
5
66
1
1
Order By: Relevance
“…Likewise, we hypothesized that IL8 rs2227307 and IL12B rs3212227 intronic polymorphisms affect alternative splicing of IL8 and IL12B mRNA and even alter mRNA expression, thereby dysregulating IL8-and IL12-mediated Th1 immune responses against fungal pathogens. In line with these arguments, a number of previous studies have reported associations of these polymorphisms with immune-related diseases (55,56) and infections (57)(58)(59)(60), including IA (45). In particular, we confirmed an association previously reported by Mezger (45).…”
Section: Discussionsupporting
confidence: 81%
“…Likewise, we hypothesized that IL8 rs2227307 and IL12B rs3212227 intronic polymorphisms affect alternative splicing of IL8 and IL12B mRNA and even alter mRNA expression, thereby dysregulating IL8-and IL12-mediated Th1 immune responses against fungal pathogens. In line with these arguments, a number of previous studies have reported associations of these polymorphisms with immune-related diseases (55,56) and infections (57)(58)(59)(60), including IA (45). In particular, we confirmed an association previously reported by Mezger (45).…”
Section: Discussionsupporting
confidence: 81%
“…This could imply that augmented IFNG expression might increase disease susceptibility. 13 Variants in some cytokines' genes are linked to modification of the risk in development of non-Hodgkin lymphoma (NHL), such as the influence of environmental factors like organochlorine exposure. Associations between studied exposures and NHL risk were limited to genotype including that of the IFNG gene (C-1615T) TT and IL4 (5 ′ -UTR, Ex1-168C>T) CC.…”
Section: Association With Human Diseasesmentioning
confidence: 99%
“…Dado que este polimorfismo ya había sido relacionado con la gravedad de otras enfermedades infecciosas (54,55), se cree que también tiene implicaciones en la malformación de megacariocitos y la diferenciación en plaquetas, predisponiendo a la trombocitopenia, como ocurre con otras fiebres hemorrágicas (56).…”
Section: Discussionunclassified